Recombinant AAV integration is not associated with hepatic genotoxicity in nonhuman primates and patients - Gil-Fariña, Irene; Fronza, Raffaele; Schmidt, Manfred (Molecular therapy, 2016)
Recombinant adeno-associated viral vectors (rAAV) currently constitute a real therapeutic strategy for the sustained correction of diverse genetic conditions. Though a wealth of preclinical and clinical studies have been conducted with rAAV, the oncogenic potential of these vectors is still controversial, particularly when considering liver-directed gene therapy. Few preclinical studies and the recent discovery of incomplete wild-type AAV2 genomes integrated in human hepatocellular carcinoma biopsies have raised concerns on rAAV safety. In the present study, we have characterized the integration of both complete and partial rAAV2/5 genomes in nonhuman primate tissues and clinical liver biopsies from a trial aimed to treat acute intermittent porphyria. We applied a new multiplex linear amplification-mediated polymerase chain reaction (PCR) assay capable of detecting integration events that are originated throughout the rAAV genome. The integration rate was low both in nonhuman primates and patient's samples. Importantly, no integration clusters or events were found in genes previously reported to link rAAV integration with hepatocellular carcinoma development, thus showing the absence of genotoxicity of a systemically administered rAAV2/5 in a large animal model and in the clinical context.